The relationship between environmental niche breadth and geographic range size across plant species. (26th November 2018) - Cardillo, Marcel; Dinnage, Russell; McAlister, William
Abstract: Aim: A positive association between environmental niche breadth and geographic range size across species (RS‐NB association) is considered a major macroecological pattern and a key mechanism explaining differences in commonness and rarity among species. It is typically assumed that niche breadth determines range size. We explore ways in which spurious positive RS‐NB associations can arise through sampling artefacts, in the absence of any ecological or evolutionary link between the two variables. Location: Australia and Africa. Methods: We used a process‐based simulation model to explore the influence of spatial autocorrelation in the environment, and the rate of neutral range evolution, on the slope of the RS‐NB association. We quantified niche breadth in four large plant genera ( Banksia, Hakea, Protea and Moraea ) using up to 12 environmental variables and accounting for variable numbers of occurrence records, and we tested RS‐NB associations using phylogenetic generalized least‐squares (PGLS) models. We compared observed patterns to two null models that break the link between species occurrences and environmental conditions in different ways. Results: The simulations show that positive RS‐NB associations are generated even under random diversification and neutral range evolution, when the environment is spatially autocorrelated. There were strong positive interspecific RS‐NB associations in all four plant genera, but in most cases, PGLS slopes for the four genera were similar to those generated by the null models. After accounting for sampling effects under the two the null models by calculating the standardized effect sizes of species' niche breadths, there was little evidence of general, positive associations between range size and niche breadth. Main Conclusions: Positive RS‐NB associations in our four plant genera do not necessarily result from an ecological or evolutionary link between niche breadth and range size but may largely reflect the historical legacy of speciation and limited dispersal, biotic interactions or other constraints on range expansion. Our results suggest that niche breadth as a general determinant of range extent among species should not be assumed without testing and correcting for spatial sampling effects.